THE EFFECT OF FINANCIAL LITERATURE AND LIFESTYLE ON STUDENT CONSUMPTION BEHAVIOR: (STUDENT CASE STUDY DEPARTMENT OF MANAGEMENT FACULTY OF ECONOMICS AND BUSINESS UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA) - Gunawan, Ade; Faadillah Carissa, Ayu (CV. Radja Publika, 2021)
This study aims to determine the effect of Financial Literacy on the Consumptive Behavior of Students at the Department of Management, Faculty of Economics and Business Universitas Muhammadiyah Sumatera Utara, to determine the effect of Lifestyle on Consumptive Behavior of Students at the Department of Management, Faculty of Economics and Business Universitas Muhammadiyah Sumatera Utara. To determine the effect of Financial Literacy and Lifestyle on Consumptive Behavior of Students at the Department of Management, Faculty of Economics and Business Universitas Muhammadiyah Sumatera Utara. The results of this study conclude that partially there is a significant influence of the Financial Literacy variable on the Consumptive Behavior of Students at the Department of Management, Faculty of Economics and Business Universitas Muhammadiyah Sumatera Utara. The results of this study conclude that partially there is a significant effect of the Lifestyle variable on the Consumptive Behavior of Students at the Department of Management, Faculty of Economics and Business Universitas Muhammadiyah Sumatera Utara. The results of this study conclude that there is a simultaneous and significant influence of Financial Literacy and Lifestyle on Consumptive Behavior of Students at the Department of Management, Faculty of Economics and Business Universitas Muhammadiyah Sumatera Utara.